Discovered Trends and Research Novelties on Iron Deficiency Anemia through Bibliometric Analysis - Santosa, Budi; Suparman,; Pranata, Satriya (Jordan Medical Journal, 2025)
Aims: This study aimed to determine the trend of the number of publications and visualization of the linkages on the topic of iron deficiency anemia through bibliometric analysis. Methods: The research method used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart. Scientific publication data related to iron deficiency anemia were retrieved via https://app.dimensions.ai/ from 2000 to 2022 and further analyzed using VOSviewer. Results: There were 143 items, 5 clusters, 4021 links, and a link strength of 47211 on the topic of iron deficiency anemia. Research trends related to iron deficiency anemia focus on genetics, knowledge, hemoglobin, and pregnant women. Suggested research topics related to iron deficiency anemia include hepatitis, disease activity, and nutrition status. Conclusion: The findings of this study can help researchers to recognize trends and novelties of research on the topic of iron deficiency anemia and recommend directions for further research.